2013
DOI: 10.1371/journal.pone.0072043
|View full text |Cite
|
Sign up to set email alerts
|

Altruism Can Proliferate through Population Viscosity despite High Random Gene Flow

Abstract: The ways in which natural selection can allow the proliferation of cooperative behavior have long been seen as a central problem in evolutionary biology. Most of the literature has focused on interactions between pairs of individuals and on linear public goods games. This emphasis has led to the conclusion that even modest levels of migration would pose a serious problem to the spread of altruism through population viscosity in group structured populations. Here we challenge this conclusion, by analyzing evolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 61 publications
1
55
0
5
Order By: Relevance
“…Individuals in each group descend from individuals in their parental group independently with probabilities proportional to f ij . That is, selection is described by a two-level Fisher-Wright framework common in theoretical studies (43). Because each group’s contribution to the next generation depends on its average fitness, this lifecycle corresponds to “hard selection” (44).…”
Section: Models and Resultsmentioning
confidence: 99%
“…Individuals in each group descend from individuals in their parental group independently with probabilities proportional to f ij . That is, selection is described by a two-level Fisher-Wright framework common in theoretical studies (43). Because each group’s contribution to the next generation depends on its average fitness, this lifecycle corresponds to “hard selection” (44).…”
Section: Models and Resultsmentioning
confidence: 99%
“…This average value has the form 1 þ OðdÞ, and therefore the absolute fitnesses have the form w à ðxÞ ¼ w 0 À dc1 A þ dbx þ Oðd 2 Þ, where w 0 is a common value for all individuals in the population in each generation.) In [13], we studied invasion in this setting, under strong or weak selection. In the relevant case for us here, in which groups are large, migration m low and selection is weak, we showed that the condition for invasion to occur is precisely (3.5), with Q ¼ 0 (see display (3.3), [13]).…”
Section: Population Structures: General Resultsmentioning
confidence: 99%
“…More detail and self-contained derivations that extend the results from [14] (2) Groups compete among themselves for the production of new groups in the next generation. This is the 'budding viscosity' population structure of Gardner & West [17], called 'propagule dispersal with group competition' in [18], and 'two-level Fisher-Wright' (2lFW) in [13]. The idea is that cooperators, at a cost to themselves, help their group in its competition with other groups.…”
Section: The Modelmentioning
confidence: 99%
“…There is evidence that moral behavior is the result of multi-level selection [13,14], but the exact mechanism is still not understood. Although the picture is not yet complete, some of its parts are gradually becoming clearer.…”
Section: Introductionmentioning
confidence: 99%